2017
DOI: 10.17338/trainology.6.2_52
|View full text |Cite
|
Sign up to set email alerts
|

Six weeks of knee extensor isometric training improves soccer related skills in female soccer players

Abstract: Objectives:Resistance training (RT) programs are often utilized to improve strength and power and thus enhance soccer performance. However, there is little research examining isometric knee extensor RTs effects upon soccer related skills. Design:The aim of this study was to examine the effects of knee extensor isometric training in female soccer athletes. Method: Sixteen female, university level, amateur soccer players (age 20.5 ± 1.1 years) were assigned to either a control or experimental group. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 21 publications
2
16
2
1
Order By: Relevance
“…However, Knapik et al [31] showed that performing 50 × 3 s isometric elbow extension at 90 ° elbow angle and 80 % MVC resulted in superior gain in isometric strength but inferior gain in isokinetic strength as compared to isokinetic strength training. Another study by Bimson et al [10] found that participants improved their countermovement jump height after performing 3 s maximal leg extension at 7 knee angles, while Kubo et al [36] found no improvement in participants who performed 10 × 15 s isometric leg press at 90 ° knee angle and 70 % MVC, even though the leg press would more likely fulfilled the training specificity principal for countermovement jump. Furthermore, the participants in the study by Bimson et al [10] were amateur female soccer players, while those in Kubo et al [36] were normal healthy adults, whose physical performance would have benefited more from any strength increment.…”
Section: Training At Multiple Joint Anglesmentioning
confidence: 98%
See 4 more Smart Citations
“…However, Knapik et al [31] showed that performing 50 × 3 s isometric elbow extension at 90 ° elbow angle and 80 % MVC resulted in superior gain in isometric strength but inferior gain in isokinetic strength as compared to isokinetic strength training. Another study by Bimson et al [10] found that participants improved their countermovement jump height after performing 3 s maximal leg extension at 7 knee angles, while Kubo et al [36] found no improvement in participants who performed 10 × 15 s isometric leg press at 90 ° knee angle and 70 % MVC, even though the leg press would more likely fulfilled the training specificity principal for countermovement jump. Furthermore, the participants in the study by Bimson et al [10] were amateur female soccer players, while those in Kubo et al [36] were normal healthy adults, whose physical performance would have benefited more from any strength increment.…”
Section: Training At Multiple Joint Anglesmentioning
confidence: 98%
“…Another study by Bimson et al [10] found that participants improved their countermovement jump height after performing 3 s maximal leg extension at 7 knee angles, while Kubo et al [36] found no improvement in participants who performed 10 × 15 s isometric leg press at 90 ° knee angle and 70 % MVC, even though the leg press would more likely fulfilled the training specificity principal for countermovement jump. Furthermore, the participants in the study by Bimson et al [10] were amateur female soccer players, while those in Kubo et al [36] were normal healthy adults, whose physical performance would have benefited more from any strength increment. These 2 comparisons suggest that performing IST at multiple joint angles would benefit dynamic and functional performance more than just performing IST at single joint angle.…”
Section: Training At Multiple Joint Anglesmentioning
confidence: 98%
See 3 more Smart Citations